Management of Sports Development Achievement of the Indonesian National Sports Committee Karo Regency, North Sumatra Province (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Management of Sports coaching on National Sports Committee of Indonesia (KONI) Karo Regency, North Sumatra Province is the most appropriate institution to coordinate all sports branch administrators in Karo Regency for athlete development programs.This research aimed to analyzed and described the planning system, the organizing system, the actuating system, the controlling system of the management activities program, funding, and infrastructure, as well as the evaluation system in KONI, Karo Regency, North Sumatra. This study used a qualitative approach with ethnographic design. The subjects in this study were administrators, coaches, athletes, and the communities at KONI Karo Regency, North Sumatra. The results of the organizational structure of management in KONI Karo Regency, North Sumatra, had a good organizational structure, and has shown an obvious line of authority with the existence of tasks under their respective fields. The activity program at KONI Karo Regency, North Sumatra, is complete and structured under the assignment decree (SK) and activities carried out according to a predetermined schedule. Funding at KONI Karo Regency, North Sumatra is not yet in a good category. Based on data on the facilities and infrastructure of KONI, Karo Regency, North Sumatra, was not yet in the good category, because it cannot support existing program activities at KONI Karo Regency, North Sumatra. Management Evaluation System at KONI Karo Regency always conducts evaluations after a match in order so that the future it can be remedied and can run according to previous planning implementation. However, it is recommended that an external party should conduct an evaluation to make a better result.